Molecular characterization of interactions between the D614G variant of SARS-CoV-2 S-protein and neutralizing antibodies: A computational approach - Kwarteng, Alexander; Asiedu, Ebenezer; Sylverken, Augustina Angelina; Larbi, Amma; Sakyi, Samuel Asamoah; Asiedu, Samuel Opoku (Infection, Genetics and Evolution, 2024)
This is an article published in Infection, Genetics and Evolution 91 (2021) 104815; https://doi.org/10.1016/j.meegid.2021.104815